Perbedaan Perilaku Konsumtif Ditinjau dari Jenis Kelamin Pada Mahasiswa Fakultas Ekonomi di Universitas Muhammadiyah Gresik - Churin In; Hasanah, Muhimmatul; Sholichah, Ima Fitri (Populer: Jurnal Penelitian Mahasiswa, 2024)
Along with ongoing economic changes and globalization, people's shopping behavior is also changing. Sometimes, someone buys something not because of need, but just for pleasure. This leads to wastefulness known as consumptive behavior. This research aims to determine the differences in consumptive behavior based on gender among students of the Faculty of Economics at Muhammadiyah University of Gresik. This type of research is quantitative research. The participants in this research numbered 285 students. The measuring instrument used is the consumptive behavior scale (Fromm, 1995). The statistical analysis method used is comparative analysis with chi-square testing. The results of this research show no difference in consumptive behavior between male and female students with a significance value of 0.840 > 0.05. The data categorization results show that the majority of subjects are at a moderate level of consumptive behavior, with a percentage of 72% for male students and 73% for female students. It is hoped that both male and female students can manage their finances as well as possible by saving and prioritizing needs over wants.